Mechanisms, advances, and challenges of immunotherapy in gastric cancer - Wang, Zixin; Wang, Tengjiao (Frontiers in Immunology, 2025)
Gastric cancer (GC) is one of the most common gastrointestinal malignancies worldwide, characterized by a high incidence rate, low screening rate, and subtle early symptoms. As a result, the majority of patients are diagnosed at an advanced or metastatic stage, contributing to poor overall prognosis. In recent years, the emergence and continuous advancement of immunotherapy have revolutionized the traditional treatment landscape for GC, offering new hope for precision medicine. Immunotherapy exerts its antitumor effects primarily by modulating the immunosuppressive tumor microenvironment and includes modalities such as immune checkpoint inhibitors (ICIs), adoptive cell therapies (ACTs), and cancer vaccines. Among these, ICIs and ACT have garnered significant attention. This review summarizes the underlying mechanisms, current applications, and major challenges of immunotherapy in GC. In addition, we discuss emerging biomarkers with potential utility for predicting immunotherapeutic efficacy in GC patients.